Epidemiology of hepatitis virus in the Colombian Amazon after 15 years of hepatitis B vaccination. (2010)
Hepatitis B virus infection (HBV) is an endemic public health problem in many countries around the globe. Latin America (LA) is considered an area of low and medium endemicity for hepatitis B infection. A highly effective vaccine has been available since the early 1980's. Colombia introduced hepatitis B vaccination (monovalent recombinant vaccine) in 1992 for children 0 to 5 living in endemic areas. In the first 10 years of the program, a reduction of 70% in carriers was found as compared to historical levels despite poor compliance with the recommended schemes. From 2001, a pentavalent vaccine of hepatitis B combined with DPT and Hib has been used with an additional dose of monovalent intended to be delivered at birth. The introduction of pentavalent has had a significant impact on the average national coverage of hepatitis B vaccine which increased from 70% to 85%. Other hepatitis viruses are also present in the region. For hepatitis A, LA countries were high endemic areas and therefore vaccination was not a pressing issue. The overall prevalence of hepatitis A infection is between 60 and 80%, but the median age of infection is around 15 years. The other enterically transmitted virus, Hepatitis E, is neglected in the Americas. Hepatitis C has been studied in the region but mostly among high risk groups such as transfusion recipients and intravenous drug addicts. Only one study from a general population has been reported from Mexico where a prevalence of 1.4% antibody positivity was found with 35% having an active infection. The present proposal aims to contribute further to evaluation of the control policy for hepatitis B infection as well as shedding light on the epidemiology of other agents of viral hepatitis in Colombia and LA. A serological population based survey will be carried out in three areas of the department of Amazon. All these places are known as high endemic areas for hepatitis B infection and historical data are available before the vaccination were introduced. The study population will be children between 1 and 10 years of age, living in rural areas of selected municipalities. A sample size of 2000 children, 1000 from each group of age (less or more than 7 years old), will be enough to test the hypothesis that the new scheme with the pentavalent has a similar effectiveness to the monovalent, since it would be able to detect even relative differences of 3% in the prevalence. That sample size also will be enough to estimate the prevalence of hepatitis E or C with a precision of 3%. The Selection criteria will be living in the study area for at least 6 months, Parental consent to participate in the study, and age between 1 and ten years. A questionnaire will be applied to collect variables related with demographic characteristics of the participants, risk factors for viral hepatitis and clinical antecedents. Vaccination dates for hepatitis B will be recorded. Serum samples will be examined by ELISA for markers of hepatitis B infection and carriage, hepatitis C, hepatitis A, hepatitis D, and hepatitis E. A sample of children negative for HB surface antigen and HB anticore will be studied for HB surface antibodies titers. HBV genome detection will be performed in serum samples corresponding to patients who present the two serological marker positive for HBV infection by ELISA (anti-HBc, HBsAg). Children will be classified as completely vaccinated if they have received at least three doses of hepatitis B vaccine, either monovalent or pentavalent. They also will be classified as timely vaccinated according to their age. Time from birth to the first dose will be taken in account for the analysis of effectiveness. The main analysis is to assess the relationship between hepatitis B vaccination characteristics and hepatitis B infection and carriage. The effect of vaccination will be assessed using Prevalence ratios (PR) and its confidence intervals (CI95%).